Peningkatan Kinerja ASN melalui Motivasi Kerja yang Dimoderasi Manajemen Talenta di Kabupaten Sukamara - Ahmat Bukori; Ibnu Khajar (Yayasan Jompa Research and Development, 2026)
This study aims to empirically analyze the influence of work motivation on human resource performance, as well as to examine the role of talent management as a moderating variable in that relationship. The type of research used is explanatory with a quantitative approach. The population in this study includes all Civil Servants (ASN) in the Sukamara Regency Government, where the sampling technique used is a saturated sampling method, resulting in a total of 134 respondents. Data were collected through a survey method using a Likert scale questionnaire from 1 to 5, which was then analyzed using the Partial Least Square (PLS) approach. Research results show that work motivation has a positive and significant effect on the performance of civil servants. However, talent management was found to negatively moderate this relationship. This means that high implementation of talent management actually weakens (rather than strengthens) the positive effect of work motivation on civil servants' performance. The practical implication of this research emphasizes that the Sukamara Regency Government needs to reevaluate the transparency of talent management implementation, so that the internal motivation of employees can synergize optimally in boosting the performance achievements of civil servants.